An Ecocritical Approach to Đuro Sudeta’s Mor—The Original Werewolf Legend - Brozović, Domagoj (Poznańskie Studia Slawistyczne, 2022)
This paper outlines the main reading strategies of ecocriticism. Its main theoretical interest lies not in the pure extraction of literary motifs of Nature, but in the deconstruction of the diversity between Nature and Culture, representing Nature as the postmodern significant “Other” relating to contemporary environmental problems and thus exposing literary approaches in the past ( including postmodernism ) as anthropocentric. The main part of this paper focuses on the example of the application of ecocritical strategies in Đuro Sudeta’s modernist and impressionistic novella Mor, which leads to the suggestion of reforming conventional readings in traditional literary history.